Densidade básica da madeira de Cecropia sp (embaúba) e sua influência na produção de celulose kraft - Heckler, Camyla [UNESP]; Sansígolo, Cláudio Angeli [UNESP]; Garcia, Felipe Manente [UNESP]; Basso, Sueza (My University, 2014)
Basic density is considered one of the most important parameters to determine the quality of wood for pulp and paper production. This study aimed to know the basic density of wood native Amazon Cecropia sp. (Embaúba), and its influence on the production of pulp and paper, the advantages and disadvantages in the process. were sampled 9 trees, taken at random in the native area of private property in the municipality of Peixoto de Azevedo, in the State of Mato Grosso. For determination of the density, was used the method of hydrostatic balance, followed by prescribed in Rule ABTCP M14/70. The species showed a basic density of 0.388 g/cm3, considered moderately light according to the classification adopted by the Forest Products Laboratory. When comparing the basic density of Cecropia sp. with Eucalyptus has on average 0.493 g / cm ³, it is clear that the Embaúba has a lower density. The density moderately light back advantages and disadvantages in the production process, influencing from the process of chopping the wood to the quality of the final product. This is advantageous in favoring the production process of chopping wood pieces, delignification and the quality of the paper, but brings disadvantages as the yield and the specific consumption of wood.

A densidade básica é considerada um dos parâmetros mais importantes para determinar a qualidade da madeira para produção de papel e celulose. Este estudo teve como objetivo conhecer a densidade básica da madeira nativa da Amazônia Cecropia sp. (Embaúba), e sua influência na produção de papel e celulose, apresentando as vantagens e desvantagens no processo. Foram amostradas 9 árvores, retiradas de forma aleatória em área nativa de propriedade particular, no município de Peixoto de Azevedo, localizada no Estado do Mato Grosso. Para determinação da densidade básica, foi utilizado o método da balança hidrostática, seguindo-se o prescrito na Norma ABTCP M14/70. A espécie apresentou densidade básica de 0,388 g/cm3 , considerada moderadamente leve segundo a classificação adotada pelo Forest Products Laboratory. Ao comparar a densidade básica da Cecropia sp. com a de Eucalyptus que tem em média 0,493g/cm³, percebe-se que a Embaúba tem uma densidade mais inferior. A densidade moderadamente leve trás vantagens e desvantagens no processo de produção, influenciando desde o processo de picagem dos cavacos até a qualidade do produto final. Esta é vantajosa no processo de produção favorecendo a picagem dos toretes, a deslignificação e qualidade do papel, porém traz suas desvantagens como no rendimento e consumo específico de madeira.
Basic density wood Cecropia sp. (embaúba) and its influence on production of kraft pulp
Keywords: Pulp and paper; Delignification; Fiber; Papel e celulose; Deslignificação; Fibras